2017
DOI: 10.1016/j.archoralbio.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic acid on collagen membranes: An experimental study in rats

Abstract: The results suggest that HA did not interfere with tissue integration and structural degradation of BioGide and Osseoguard™ membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 36 publications
3
17
0
Order By: Relevance
“…Histological findings have shown that the immersion in a cross‐linked HA gel did not interfere with the structure and degradation of the collagen membranes or soft tissue invasion into it. Our findings are in line with the results from another study in normoglycemic rats showing that HA did not interfere with tissue integration and structural degradation of collagen membranes …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Histological findings have shown that the immersion in a cross‐linked HA gel did not interfere with the structure and degradation of the collagen membranes or soft tissue invasion into it. Our findings are in line with the results from another study in normoglycemic rats showing that HA did not interfere with tissue integration and structural degradation of collagen membranes …”
Section: Discussionsupporting
confidence: 92%
“…Our findings are in line with the results from another study in normoglycemic rats showing that HA did not interfere with tissue integration and structural degradation of collagen membranes. 28 On one hand, the present study has shown that immersion in HA gel resulted in delayed degradation of the CM in uncontrolled STZ-induced diabetic rats. On the other hand, this effect was not demonstrated in the normoglycemic group, since HA-and PBSimmersed CMs showed no statistically significant differences regarding residual collagen membrane content and thickness.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…While this implies loss of integrity as a barrier, at the same time the membrane was able to support the bone regeneration process and to create an environment that promoted the deposition and mineralization of the bone matrix, with blood vessels penetrating throughout the membrane at 30 days. A recent study in a similar calvaria defect model also confirmed that, at 30 days of healing, the collagen membrane network is progressively invaded by areas of bone formation and presents a dense infiltrate of leukocytes and fibroblast‐like cells …”
Section: Discussionmentioning
confidence: 62%
“…Ideally, the biomaterials should be radiolucent, so that bone formation in the defect can be detected and even monitored by μCT. Pioneer knowledge on the osteoconductive properties of collagen membranes in rat calvaria (Silva et al., ; Song et al., ) and maxillary defects (Taguchi et al., ) has been generated. The collagen membrane used here is composed of porcine type I collagen and type III collagen and has a bilayer structure with a dense and a spongy layer (Bio‐Gide).…”
Section: Introductionmentioning
confidence: 99%